2019
DOI: 10.1002/chem.201900492
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Dynamics Underlies Different Functions of Human KDM7 Histone Demethylases

Abstract: The human KDM7 subfamily histoneH 3N emethyll ysine demethylases PHF8 (KDM7B) and KIAA1718 (KDM7A) have different substrate selectivities and are linked to genetic diseases and cancer.W ed escribe experimentally basedc omputational studies revealing that flexibility of the region linking the PHD finger and JmjC domains in PHF8 and KIAA1718 regulates interdomain interactions, the nature of correlated motions, and ultimately H3 binding and demethylation site selectivity.F 279S an Xlinked mental retardation mutat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 24 publications
0
33
0
Order By: Relevance
“…The mechanisms of dioxygen activation by non‐heme Fe (II) enzymes have been explored using experimental and computational methods; [2,12–14] however, there are no such studies reported on the recently reported JmjC KDM catalyzed histone arginine demethylation (RDM) reaction [15–17] . The 2OG oxygenases have evolved to activate O 2 to enable production of a ferryl intermediate that effects C−H bond cleavage, typically generating an alcohol product [7,12–14] .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The mechanisms of dioxygen activation by non‐heme Fe (II) enzymes have been explored using experimental and computational methods; [2,12–14] however, there are no such studies reported on the recently reported JmjC KDM catalyzed histone arginine demethylation (RDM) reaction [15–17] . The 2OG oxygenases have evolved to activate O 2 to enable production of a ferryl intermediate that effects C−H bond cleavage, typically generating an alcohol product [7,12–14] .…”
Section: Introductionmentioning
confidence: 99%
“…The 2OG oxygenases have evolved to activate O 2 to enable production of a ferryl intermediate that effects C−H bond cleavage, typically generating an alcohol product [7,12–14] . Details of the mechanism leading to the ferryl intermediate and studies on model systems have been reported [15– 26a] . Following substrate binding, the consensus 2OG oxygenase mechanism [7,12– 26a–c] involves initial generation of a Fe(III)‐superoxo complex; oxidative decarboxylation of 2OG generates a Fe(II)‐peroxysuccinate intermediate which reacts to give a high‐spin (S=2) state ferryl intermediate, which abstracts a hydrogen atom from the substrate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The JmjC-type KDMs are one group of α-ketoglutarate-dependent oxygenases that catalyze a remarkably diverse range of oxidative reactions [ 9 ]. The JmjC-type KDMs remove methyl groups on lysine in the specific amino acid stretches of histones, and the selectivity of substrates is determined by the structure of the JmjC domain and also the dynamics of the amino acid sequence near the JmjC domain [ 10 , 11 ]. KDMs also distinguish the number of methyl groups attached to lysine [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The KDM7 enzymes have a PHD domain at the N-terminal, and JmjC at the C-terminal, both domains are dispensable for removing methyl group from H3K91/2. The KDM7A and KDM7B differ in flexibility and the length of their linker region (Chaturvedi et al 2019a(Chaturvedi et al , 2019b (Table 2). To be brief, H3K9 methyltransferases and demethylases act as 'writers' and 'erasers' to precisely balance H3K9 methylation status.…”
Section: Properties Of H3k9 Methyltransferases and Demethylasesmentioning
confidence: 99%